PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP LIKUIDITAS - Ajeng Lestari; Itat Tatmimah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2019)
Abstract - This study aims to determine: the effect of cash turnover on liquidity and the influence of accounts receivable turnover on liquidity. The research method used in this research is descriptive using secondary data, the population in this study are all manufacturing companies of various industry sectors listed on the Indonesia Stock Exchange in 2016 until 2018. Sampling was done using the purposive sampling method until 33 companies were obtained the sample. Based on the results of multiple regression analysis, it can be concluded that the level of cash turnover does not significantly influence liquidity in various industry sector manufacturing companies listed on the Indonesia Stock Exchange, accounts receivable turnover also does not affect the liquidity of various industry sector manufacturing companies listed on the Indonesia stock exchange. Simultaneous accounts receivable turnover and inventory turnover have no significant effect on the liquidity of various industry sector manufacturing companies listed on the Indonesia Stock Exchange. Keywords: liquidity, cash turnover, accounts receivable turnover